Adoption of Information Technology and its Implications for The Operational Efficiency of Micro, Small, and Medium Enterprises - Tanty Yuanita; Bambang Bernanthos (Jurnal Multidisiplin Indonesia, 2025)
The digitalization era has transformed the global business landscape, including the Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia. This study analyzes the impact of information technology adoption on operational efficiency of MSMEs using quantitative approach through surveys of 250 MSMEs in Central Java. Data were analyzed using Structural Equation Modeling (SEM) to examine relationships between information technology adoption variables and operational efficiency. Results indicate that information technology adoption has significant positive effect on MSME operational efficiency with determination coefficient of 0.742. Implementation of point-of-sale systems, e-commerce, and digital inventory management proved to increase operational productivity by 35.6% and reduce operational costs up to 28.4%. Factors influencing adoption include business owner digital literacy, infrastructure support, and financial capacity. These findings provide strategic implications for MSME digitalization policy development and digital transformation strategies for small and medium enterprise sector in Indonesia.